PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN DI DINAS PERIKANAN DAN KETAHANAN PANGAN KOTA DENPASAR - Ni Made Ayu Saisa Ganesh Mahanami; Gde Bayu Surya Parwita; Tiara Carina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
The background of this research stems from the phenomenon of declining employee productivity, which is reflected through an increase in attendance tardiness, decreased work enthusiasm, and a lack of initiative among employees in completing tasks. In addition, there are indications of weak implementation of organizational culture, low work discipline, and suboptimal job satisfaction levels. This study is expected to provide empirical contributions to understanding internal factors that influence employee productivity within government institutions, particularly in the Dinas Perikanan dan Ketahanan Pangan Kota Denpasar. The population in this study consists of 35 employees, who are staff members of Dinas Perikanan Kota Denpasar. The sampling technique used is a saturated sample, resulting in a total of 35 respondents. The research method applied is quantitative, with data analysis techniques including validity testing, reliability testing, non-parametric testing using Spearman’s Rho, and ordinal regression analysis using SPSS version 29. The results of the study show that organizational culture has a positive and significant effect on employee productivity at Dinas Perikanan dan Ketahanan Pangan Kota Denpasar. Work discipline also has a positive and significant effect on employee productivity, and job satisfaction influences employee productivity at Dinas Perikanan Kota Denpasar. The suggestions provided for future research include maintaining the implementation of positive organizational culture values, improving a consistent and fair work discipline system, paying attention to factors that can enhance job satisfaction, and expanding the scope of research by adding other variables that may influence employee productivity.